Physical activity to prevent older adult falls: an Aotearoa New Zealand approach - Lara Vlietstra; Katrina Pōtiki Bryant; Leigh Hale; Margaret Dando; Debra Waters (Revista Brasileira de Atividade Física e Saúde, 2025)
Physical activity and exercise decreases falls by improving gait, balance, and strength. All types of exercise, particularly balance and functional exercises reduce the rate of falls by approximately 24%, although walking practice alone does not reduce falls rate. New Zealand has developed three effective, empowering and sustainable falls-prevention exercise classes for older adults. The world-renowned, home-based Otago Exercise Programme, the peer-led community-based Steady As You Go© and Aligned to Go, and Taurite Tū indigenous exercise program. The majority of the exercises are conducted while standing and progress to where the participant stands with feet close together, on one leg, minimises hands assisting with balance, and practice controlled movements of the body’s centre of mass and body awareness. Peer-led classes such as Steady As You Go©, Aligned to Go and Taurite Tū have demonstrated their ability to attract participants to engage long term through strong social connections and culturally appropriate exercises that enable older adults to maintain their balance, strength and reduce their falls risk.